Immobilized Aspartase-Containing Microbial Cells: Preparation and Enzymatic Properties - Chibata, Ichiro (1974)
The immobilization of asparatase-containing Escherichia coli was investigated by various methods, and the most active immobilized cells were obtained by entrapment in a polyacrylamide gel lattice. Other asparatase-containing bacteria were also entrapped by the same method, and the enzymatically active immobilized cells were obtained. The aspartase activity of the immobilized E. coli cells was increased nine- to tenfold by autolysis of the cells entrapped in the gel lattice. Enzymatic properties of the immobilized E. coli cells were investigated and compared with those of the intact cells. The optimal pH was 8.5 for the immobilized cells and 10.5 for the intact cells. The aspartase activities of immobilized and intact cells were not activated by Mn(2+), which can activate the immobilized and native aspartases. The heat stability of the immobilized cells was somewhat higher than that of the intact cells. Bivalent metal ions such as Mn(2+), Mg(2+), Ca(2+) protected against thermal inactivation of the aspartase activity of the immobilized and intact cells.